Teleworking in the UGPP (2014)
This study conducted an analysis to the administrative impact on UGPP in Bogota. To this end, the International Telework national context with satisfactory results for workers in Colombia since the establishment of the rule of law 1221 of 2008 issued by the Ministry of Labour was characterized. In addition to implementing the strengths of this new form of employment in major companies and an ongoing evaluation of it was taken.